Certain Tamil Film Songs Belong to Yester Year Actors Such as Thyagaraja Bagavathar, N.S. Krishnan, Chandra Babu, Gemini Ganesan, Asokan, Nagesh, Jaishankar and Muthuraman Contains Ethical Imports that can be Compared with Ethical Theories - A Retrospective Reflection (Global Journal of Human-Social Science, 2025)
This research work is being undertaken to find out whether cetain film songs by famous Tamil film actors of yester years such as THYAGARAJA BAGAVATHAR N S KRISHNAN CHANDRABABU GEMINI GANESAN ASOKAN NAGESH JAISHANKAR AND MUTHURAMAN cotain ethical import The ethical ideas that contain in the film songs were grouped and a comparative analysis to the relevant theories more specifically the ethical theory enunciated by W D Ross were made using a novel methodology The selection of songs has been made out from the selected movies acted by these eminent actors As the present work is about the above eight eminent actors it has been decided to discuss about them under each chapter thereby this work contains eight chapters Each chapter will consist of brief biography of the Hero and the contexts that evaluates the songs relating to them that could be compared with ethical import